Changes in Dietary Inflammatory Index Score over Time and Cancer Development in Rural Post-Menopausal Women - Mariah Kay Jackson; Joan Lappe; Jihyun Ma; Megan Timmerman; Elizabeth R. Lyden; Nitin Shivappa; James R. Hébert; Dianne Travers Gustafson; Laura Graeff-Armas; Corrine Hanson (MDPI AG, 2023)
Inflammation plays a key role in cancer development. As an important modulator of inflammation, the role of diet should be explored. The purpose of this study was to determine the association between diets with a higher inflammatory potential, as measured by the Dietary Inflammatory Index (DII®), and cancer development in a cohort of rural post-menopausal women. Dietary intake from a randomized controlled trial cohort of rural, post-menopausal women in Nebraska was used to compute energy-adjusted DII (E-DIITM) scores at baseline and four years later (visit 9). A linear mixed model analysis and multivariate logistic regression evaluated the association between E-DII scores (baseline, visit 9, change score) and cancer status. Of 1977 eligible participants, those who developed cancer (n = 91, 4.6%) had a significantly larger, pro-inflammatory change in E-DII scores (Non-cancer: Δ 0.19 ± 1.43 vs. Cancer: Δ 0.55 ± 1.43, p = 0.02). After adjustment, odds of cancer development were over 20% higher in those with a larger change (more pro-inflammatory) in E-DII scores than those with smaller E-DII changes (OR = 1.21, 95% CI [1.02, 1.42], p = 0.02). Shifting to a more pro-inflammatory diet pattern over four years was associated with increased odds of cancer development, but not with E-DII at baseline or visit 9 alone.